2019
DOI: 10.1016/j.sjbs.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in tilapia populations in a freshwater reservoir assayed by randomly amplified polymorphic DNA markers

Abstract: Genetic variation in fish stocks decreasing due to water pollution in the freshwater rivers, streams and canals. The objective of this study was to determine the genetic diversity and polymorphism in Oreochromis niloticus collected from the Wadi Hanefah Riyadh, Saudi Arabia by using RAPD-PCR. Total thirty fish specimens were harvested from each of four pre-determined locations of the reservoir which were designated as H1, H2, H3, and H4. Five random decamer primers were used to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The genetic variability observed might be due to aquatic pollution that have probably occurred over a long period of time in the waterbodies studied. This observation is consistent with a previous report on RAPD analysis of O. niloticus from various locations in Riyadh river which revealed genetic diversity in the fish population studied (47). Previous reports have suggested that Apodu, Oyun and Moro rivers may contain several types of aquatic pollutants which may be one of the reasons for genetic variability observed among fish populations in these studied waterbodies (48)(49)(50).…”
Section: Discussionsupporting
confidence: 92%
“…The genetic variability observed might be due to aquatic pollution that have probably occurred over a long period of time in the waterbodies studied. This observation is consistent with a previous report on RAPD analysis of O. niloticus from various locations in Riyadh river which revealed genetic diversity in the fish population studied (47). Previous reports have suggested that Apodu, Oyun and Moro rivers may contain several types of aquatic pollutants which may be one of the reasons for genetic variability observed among fish populations in these studied waterbodies (48)(49)(50).…”
Section: Discussionsupporting
confidence: 92%
“…The spacious range of the band size was comparable with previous studies, where 5 RAPD markers produced 45 amplicon, (250-2000 bp) in Eutropiichthys vachapopulation (Chandra et al 2010). The six RAPD primer produced 48 and 44 scorable bands in tilapia (Mahboob et al 2019;Khafaji et al 2019), 16 RAPD markers generate 197 bands ranged from 114-2000 bp in six golden mahseer populations (Sha et al 2016) and 12 RAPD primers produced 87 bands, ampli ed band ranged from 400-1250 bp in four Rohu populations (Kabir et al 2017). Moreover the present studies was corelated with the previous studies Vasave et al 2014 (rainbow trout and snow trout), Hasan and Goswami 2015 (cat sh (Mystus vittatus)), and six RAPD prime produced 89 and 60 ampli ed bands with 50-1500 bp in genetic analysis of Capoeta copeta gracilis and piracanjuba sh population (; Lopera-Barrero et al 2019) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the species are considered to be endangered due to the declining of their natural habitat and also reduced in numbers and sizes of populations. The crucial factors responsible for the decline in the number and size of different sh population involve alternation of climate and habitat, pollution, dam construction, fragmentation, eutrophication, replacement of invasive or intentionally introduced species, over-shing, the aquarium pet trade, river ow modi cation, and even the consideration of the most optimistic climate change scenario points to the likelihood of ex-situ management of many species for their survival (Jeong et al 2012;Kelly et al 2013;Reis 2013;Gupta and Homechudhuri 2015;Gallardo et al 2016, Pauly andZeller 2016;Medeiros et al, 2016;Gold et al, 2017;Santos et al, 2017;Filho et al 2018;Martinz et al 2018;Mahboob et al 2019;Lopera-Barrero et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, genetic characterization of strains and species of tilapia has been widely used for the identification of economically desired traits for aquaculture production [14] [15] [16] [17] [18]. Most of studies on genetic characterization on Nile tilapia used the variations of various genetic markers [16] [19] [20] including microsatellites and SCARs [16] [21] [22] [23] [24] [25] to assess and compare genetic diversity and differentiation of farmed populations. In this study, five SSR and one SCAR (SCARII) markers were used to assess the genetic diversity and structure of five populations of from different localities of Senegal.…”
Section: Introductionmentioning
confidence: 99%